Sustainable Dry Turning of Aluminum Alloys Using Pulsed High-Pressure Cryogenic Jet Cooling - Selzam, Jan Harald; Enslein, Niklas; Gross, Daniel; Hanenkamp, Nico (Lecture Notes in Mechanical Engineering, 2025)
As well as producing contamination-free parts, dry machining is a sustainable alternative to conventional machining processes using metalworking fluids. Despite these benefits, chip breaking and chip removal are challenges in dry machining processes, particularly when turning ductile materials, which are known for continuous chip formation and therefore long chips. Due to their tendency to become entangled around machine components, these chips have to be removed manually, posing a risk to productivity and operator health. Recent studies have demonstrated the effectiveness of pulsed high-pressure emulsion cooling for chip breaking. This paper aims to transfer these findings to sustainable dry machining and investigates the influence of pulsed high-pressure cryogenic jet cooling on chip breaking and chip removal. Therefore, liquid CO2 at pressures up to 200 bar is used as a cooling medium in turning processes of two aluminum alloys and is applied continuously or pulsed to the machining area. It has been shown that high-pressure cryogenic jet cooling improves chip breaking and chip removal, allowing a wider range of cutting parameters, widening the process window and providing a higher level of sustainability, productivity and safety in dry machining.
CRIS-Team Scopus Importer:2025-02-28
Keywords: Aluminum; Carbon dioxide; Dry turning; Pulsed high-pressure cryogenic jet cooling; Sustainable machining